Aconite Poisoning: A Case Report - Maharjan, sumi; Raman Parajuli, Sudhir; Dhungana, Durga (Annapurna Journal of Health Sciences, 2023)
Aconite is the well-known toxic plant as well as valuable drug since decades. Most of the intoxications are accidental whereas suicidal attempt is rather rare after ingestion. This case report is about two patients who landed in our emergency department after consuming Aconite accidentally as an herbal medicine and were managed immidiatley.